Strategie komunikacyjne w służbie apoteozy przeszłości w prozie historycznej Zofii Bukowieckiej z okresu zaborów = Communication strategies in the service of the past apotheosis in Zofia Bukowiecka's historical prose from the partitions period - Hawrysz, Magdalena (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The aim of the sketch is to identify writing strategies and the repertoires of linguistic means used in the apotheosizing description of the state that emerges from Zofia Bukowiecka's historical prose. Creation of a laudatory vision of Poland's past (in accordance with the guidelines of the era) is created by Z. Bukowiecka purposively and is of an educational, comforting, and finally - the most importantly - formative nature, i.e. it aims to awaken patriotic attitudes in a nation which was de?prived of the state.
Keywords: strategie komunikacyjne; świadomość narodowa; zabory; proza historyczna dla dzieci; Bukowiecka, Zofia (1844-1920); communication strategies; national consciousness; partitions; historical prose for children